AYAT-AYAT AL-QURAN TENTANG PEMELIHARAAN LINGKUNGAN - Tajul Aripin, Ipin (Ahwaluna | Jurnal Hukum Keluarga Islam, 2025)
The environment is a vital aspect of human life, yet it is currently deteriorating due to climate change, pollution, and biodiversity loss. Islam, as a comprehensive religion, provides guidance on human responsibility in environmental conservation, as outlined in the Qur’an. This study aims to analyze ecological values in the Qur’an through a literature review and hermeneutic analysis. The findings indicate that the Qur’an emphasizes the principles of ecosystem balance, sustainability, prohibition of destruction, and human responsibility as stewards of the earth. Several verses discuss the obligation to maintain ecological balance and the prohibition of causing damage after the earth has been restored. Additionally, the concept of sustainability is reinforced by the command to avoid excessive consumption of resources. Islam also teaches awareness of the magnificence of creation as a sign of God's greatness, which must be preserved as an expression of gratitude. These principles provide an ethical foundation for pro-environmental behavior among Muslims. However, the implementation of these teachings is often influenced by social and economic factors. By understanding the environmental values in the Qur’an, it is hoped that society will become more aware of the importance of preserving nature as an act of worship and moral responsibility. Keywords: environment, Qur’an, ecosystem balance, sustainability, stewardship